Perlindungan Anak dalam Perspektif Islam - Ahmad, Zulfa (Program Pascasarjana UIN Sunan Ampel Surabaya, 2009)
This paper deals with the problem of child protection from an Islamic perspective. It starts by discussing the Islamic teaching concerning family values and the function of family in child education as well as the responsibility of the family in protecting the children. By extension the paper is also concerned with the idea of marriage, its meaning and function in social life. We base our analysis on the QurâÃ¢nic verses but also on the child protection law number 23 year 2002. We basically argue that it is up to the family to raise the children in a positive or negative manner. The very structure of family is very much relevant to the upbringing of the children and that their positive or negative attitude is dependent upon the nature of the surrounding in which they live.